ANALISIS STUDI KELAYAKAN USAHA PENDIRIAN HOME INDUSTRY (Studi Kasus pada Home Industry Cokelat “Cozy” Kademangan Blitar) - Abidatul Afiyah (Fakultas Ilmu Administrasi Universitas Brawijaya, 2015)
Chocolate Home Industry “Cozy” is a new business established by self funding, with amounted of money Rp10,000,000. The products are cocoa powder and chocolate bar with a variety of flavors. This research aims to determine the feasibility of investment in the establishment of Chocolate Home Industry “Cozy” where located at Jaten RT 01 RW 01 Kademangan Blitar. The research was conducted in January-February 2015 using data collection techniques such as observation, interviews, and documentation. The technical and production aspects, organization and management aspects and also financial aspects with the calculation of the feasibility of investment such as Payback Period (PP), Net Present Value (NPV), Internal Rate of Return (IRR), and Profitability Index (PI). Market and marketing analysis indicates that prospects for Chocolate Home Industry “Cozy” is good enough, it is seen from the increasing number of demand every year. Technical analysis and production showed that the location of the home industry is close to the residental allows them to recruit labors. Organization and management analysis shows that business owner has been running the management functions well, starting from planning, organizing, directing, and controlling. The result of financial analysis showed that Payback Period (PP) of that business is 1 year and 7 months, the Net Present Value (NPV) is 116.261.950, the Internal Rate of Return (IRR) is 116,33%, and the Profitability Index (PI) is 12,63. Keywords: Home Industry, The Feasibility Study, Aspects of Feasibility Study ABSTRAK Home Industry Cokelat “Cozy” merupakan usaha baru yang didirikan dengan modal sendiri, yaitu sebesar Rp10.000.000. Produk yang dihasilkan berupa cokelat bubuk dan cokelat batang dengan berbagai macam varian rasa. Penelitian ini bertujuan untuk mengetahui tingkat kelayakan investasi dalam pendirian Home Industry Cokelat “Cozy” yang beralamat di Lingkungan Jaten RT 01 RW 01 Kelurahan Kademangan Kecamatan Kademangan Kabupaten Blitar. Penelitian dilaksanakan pada Bulan Januari-Februari 2015 dengan teknik pengumpulan data berupa observasi, wawancara, dan dokumentasi. Metode yang digunakan yaitu aspek pasar dan pemasaran, aspek teknis dan produksi, aspek organisasi dan manajemen, serta aspek finansial dengan perhitungan kelayakan investasi berupa Payback Period (PP), Net Present Value (NPV), Internal Rate of Return (IRR), dan Profitability Index (PI). Analisis pasar dan pemasaran menunjukkan bahwa prospek Home Industry Cokelat “Cozy” cukup baik, dilihat dari peningkatan jumlah permintaan setiap tahun. Analisis teknis dan produksi menunjukkan bahwa lokasi home industry dekat dengan pemukiman sehingga memudahkan untuk merekrut tenaga kerja. Analisis organisasi dan manajemen menunjukkan pemilik usaha telah menjalankan fungsi manajemen dengan baik. Analisis finansial dengan menggunakan 100% modal sendiri didapatkan hasil Payback Period (PP) yaitu 1 tahun 7 bulan, Net Present Value (NPV) sebesar 116.261.950, Internal Rate of Return (IRR) sebesar 116,33%, dan Profitability Index (PI) sebesar 12,63. Kata Kunci: Home Industry, Studi Kelayakan, Aspek-aspek Studi Kelayakan Bisnis